WEBSITE IMPLEMENTATION AS AN INFORMATION SYSTEM FOR SALES OF AGRICULTURAL PRODUCTION FACILITIES IN KELUBIR VILLAGE, NORTH KALIMANTAN - Syaifudin Fery Maulana; Falaah Abdussalaam (INFOKOM (Informatika & Komputer), 2025)
The purpose of this research is to implement a website as an information system for the sale of agricultural production facilities, which can be used by the community to find suitable agricultural medicines for farmers in Kelubir Village. This website is designed to facilitate farmers in purchasing or conducting agricultural transactions and to provide information related to the required production facilities. The research method used involves an approach to farmers by collecting data through interviews, observations, and documentation studies. The results of this study indicate that the implementation of the website can facilitate and improve the efficiency of selling agricultural production facilities and accelerate access to information about agricultural production facilities. This website is expected to be an effective solution in supporting the development of the agricultural sector in Kelubir Village and strengthening the local economy in the village.